2020
DOI: 10.1099/jmm.0.001189
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of yeast species causing bloodstream infection in Tehran, Iran (2015–2017); superiority of 21-plex PCR over the Vitek 2 system for yeast identification

Abstract: Introduction. Given the limited number of candidaemia studies in Iran, the profile of yeast species causing bloodstream infections (BSIs), especially in adults, remains limited. Although biochemical assays are widely used in developing countries, they produce erroneous results, especially for rare yeast species. Aim. We aimed to assess the profile of yeast species causing BSIs and to compare the accuracy of the Vitek 2 system and 21-plex PCR. Methodology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
1
19
4
1
Order By: Relevance
“…albicans constituted 79% of the isolates and was the most abundant Candida species responsible for VVC and RVVC. This observation is consistent with previous studies on VVC ( Sharifynia et al, 2017 ; Ghajari et al, 2018 ), oral candidiasis ( Arastehfar et al, 2019a ), and candidemia ( Arastehfar et al, 2020d ; Kord et al, 2020 ) in Iran, which documented the abundance of C. albicans among Iranian patients, whereas C . glabrata was reported the most prevalent Candida species among Indian patients ( Mohanty et al, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…albicans constituted 79% of the isolates and was the most abundant Candida species responsible for VVC and RVVC. This observation is consistent with previous studies on VVC ( Sharifynia et al, 2017 ; Ghajari et al, 2018 ), oral candidiasis ( Arastehfar et al, 2019a ), and candidemia ( Arastehfar et al, 2020d ; Kord et al, 2020 ) in Iran, which documented the abundance of C. albicans among Iranian patients, whereas C . glabrata was reported the most prevalent Candida species among Indian patients ( Mohanty et al, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although Candida albicans has been historically known as the most prevalent causative agent of fungal vulvovaginitis, new lines of evidence reveal an increasing incidence of non- albicans Candida (NAC) species, which generally respond to higher MICs of azoles ( Makanjuola et al, 2018 ) and which may contribute to complications associated with RVVC. Since the vast majority of RVVC cases are recorded in developing countries ( Denning et al, 2018 ), the shift toward NAC species could be problematic for their healthcare institutions, where the diagnosis and treatment of fungal infections are inadequate ( Arastehfar et al, 2019a , b , c , d ; Arastehfar et al, 2020d ; Kord et al, 2020 ; Megri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, 40.7% of our patients were not treated with antifungal drugs. This result disagrees with other studies that reported uconazole was the most antifungal drug received in candidemia patients (21,22). The low mortality rate (14.8%) were obtained in our study was mostly lower than other reported in Iran (28-47%) (21,22).…”
Section: Discussioncontrasting
confidence: 99%
“…This result disagrees with other studies that reported uconazole was the most antifungal drug received in candidemia patients (21,22). The low mortality rate (14.8%) were obtained in our study was mostly lower than other reported in Iran (28-47%) (21,22). It seems that this difference may due to different conditions of candidemia patients such as underlying disease, antifungal therapy, the type of Candida species, and the length of hospitalization.…”
Section: Discussioncontrasting
confidence: 99%
“…Drug exposure included the recorded data of the preceding six months and if needed records of the previous hospitalizations were checked. Thirty-day mortality was defined when death occurred ≤ 30 days after the first positive blood culture ( Kord et al., 2020 ). Candida parapsilosis blood isolates were inoculated onto Sabouraud glucose agar (Merck, Darmstadt, Germany) and chromogenic agar (Candi Select ™ 4, Bio-Rad, Hercules, CA, USA) plates and incubated at 37°C for 24–48 h. Species identification was performed using primers targeting internal transcribed spacer 1 (ITS1; TCCGTAGGTGAACCTGCGG) and ITS 4 (GCATATCAATAAGCGGA) ( Stielow et al., 2015 ).…”
Section: Methodsmentioning
confidence: 99%